Draft Annual Plan 1986-87 Vol. II Uttar Pradesh - Planning Commission (Planning Commission, 1985)
Statement head of development outlays and expenditure major head of development—agriculture and allied services major head of development—rural development major head of development—special area programmes major head of development—irrigation and flood control major head of development—energy major head of development-industry and minerals major head of development—transport major head of development-science, technology and environment major head of development—general economic services
Government of Uttar Pradesh, Planning Department